2013
DOI: 10.1227/neu.0b013e31828bf342
|View full text |Cite
|
Sign up to set email alerts
|

Distraction, Compression, and Extension Reduction of Basilar Invagination and Atlantoaxial Dislocation

Abstract: BACKGROUND: The management of basilar invagination (BI) and atlantoaxial dislocation (AAD) is a challenge. OBJECTIVE: To describe a new innovative method to reduce BI and AAD through a single-stage posterior approach. METHODS: Thirty-five patients had irreducible BI and AAD (May 2010 to April 2012). In all patients, reduction of AAD and BI was achieved by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 50 publications
2
91
0
Order By: Relevance
“…The main characteristic of incongruence is represented by the disruption of this relationship, which was assessed in this study in CT multiplanar images of all affected patients. The combined diagnostic approach described herein, which included both CT and MRI, is consistent with the described approach recently described in veterinary research and used in human medicine for complete evaluation of the cranio-spinal junction [8,14,16,25].…”
Section: Discussionmentioning
confidence: 90%
“…The main characteristic of incongruence is represented by the disruption of this relationship, which was assessed in this study in CT multiplanar images of all affected patients. The combined diagnostic approach described herein, which included both CT and MRI, is consistent with the described approach recently described in veterinary research and used in human medicine for complete evaluation of the cranio-spinal junction [8,14,16,25].…”
Section: Discussionmentioning
confidence: 90%
“…Recently, several reports (4,8,24,28) have claimed that posterior fixation is an effective method to treat AAD and …”
Section: █ Discussionmentioning
confidence: 99%
“…According to these reports, occipitocervical fusion and C1 and C2 fusion are two main fixations. Chandra et al (4) reported that using an innovative method of distraction and spacer placement followed by compression and extension can reduce AAD and BI. Goel et al (15) used of the plate and screw method (C1/2 fusion) of fixation in the treatment of 160 patients with atlantoaxial instability and achieved good outcomes with low incidence of complications.…”
Section: Surgical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Often these dislocations are irreducible and may have additional non-correctable rotational and lateral components. The recent trend has shifted from traditional transoral decompression and posterior fusion to a direct posterior release of facets and reduction of dislocation [2][3][4][5][6][7][8]. Correction of all the components of dislocation and fixation in realigned position is desirable.…”
Section: Introductionmentioning
confidence: 99%